Multi-Frequency Wideband Microstrip Patch Antenna for Wireless Applications - Kaur, Jaswinder (My University, 2014)
Remarkable equipment development in the field of communication and the growing end user requirement has lifted the need for multi-functional wireless communication devices. Since the antenna is the most basic part of each wireless communication scheme, therefore, multi-functional antennas are looked for to meet up the present day requirements. The antennas are so designed that these could be able to sustain compound functions in a particular single antenna system rather than sustaining one operational frequency. For this reason multiband/multi-frequency/multi-standard antennas can be used basically to lessen the amount of antennas needed for any projected system application. The purpose of this thesis is to investigate novel methods to develop microstrip patch antennas (MPAs) that exhibit multi-frequency/wideband behavior. Because of the rapid advancements in the industry of wireless communication, original and new antenna design structures that could be utilized in more than one single frequency band and those that permit size reduction are in great essential activity. For example, services relating mobile telephony need conveniently transported devices congenial with Global System for Mobile Communication (GSM)/Digital Cellular Service (DCS)/Universal Mobile Telecommunications System (UMTS) technology and the afore mentioned equipment should also colligate the users to Wireless Local Area Network (WLAN) networks established on 2.5 GHz/5 GHz communication standards. Thus, the design of compact antennas suited for these devices is of extraordinary concern. Several techniques have been suggested for the design of radiating elements of this type, the relatively large majority of which are microstrip antennas. An ordinary feature of virtually the whole of the multi-frequency printed elements is that they generally come from an initial patch of common shape which is perturbed in the succeeding stage. Depending upon the method of shape perturbation or disturbance, the development and analysis of multi-frequency/multi-standard microstrip antennas can be carried out. The design aims of getting an appreciable reflection coefficient, wide impedance bandwidth, increased gain, perfect impedance matching, increased frequency ratio and reasonable antenna size with multi-frequency operation are considered as the main goals of the present thesis. This thesis describes original work done for getting multi-frequency and wideband behavior of microstrip antennas. Microstrip antennas suffer from many constraints on their performance. One major restriction is their narrow impedance bandwidth. An effective method to resolve this is adding more resonators and slots to the antenna structure to achieve multi-resonance and hence wider bandwidth. Bandwidth can also be increased using a Defected Ground Structure (DGS). On the basis of dimensions and shape of the defect in the ground plane, the protected distribution of current density in the ground plane is interrupted, leading to a restrained excitation and generation of the electromagnetic waves through the substrate layer that modify the characteristic properties of the transmission line. The shape of the defect may be changed from a simple shape to the complicated shape for getting the desired performance as discussed in chapters three. Also, by making slight modifications in the conducting patch and ground structures in the form of slits or slots, excitation of an additional resonance beside the fundamental resonating frequency can be allowed as discussed in chapter four. The current distribution may be changed accordingly. With the correct coupling between the resonant modes, the impedance bandwidth can be significantly increased. Furthermore, four more novel antenna designs with their simulated reflection coefficient and radiation pattern results have been presented in chapter five. Overall, all the proposed six antenna designs presented in chapters three, four and five are capable of exhibiting dual or multi-frequency wideband or broadband behavior. This whole research is verified through analytical simulations using three dimensional electromagnetic simulator - Computer Simulation Technology Microwave Studio Version 9.0 (CST MWS V9.0). Experimental investigations and measurements have been carried out using Vector Network Analyzer (VNA) available in Microwave and Antenna Laboratory, T.U., Patiala and Anechoic Chamber available in Millimeter Wave Laboratory, I.I.T., Roorkee.
PHD, ECED
Keywords: Microstrip patch Antenna, defected ground structure, slotted structures; wireless applications